The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2016
DOI: 10.1103/physreve.94.043103
|View full text |Cite
|
Sign up to set email alerts
|

Connections between centrifugal, stratorotational, and radiative instabilities in viscous Taylor-Couette flow

Abstract: This is the final published version of the article (version of record). It first appeared online via APS at http://journals.aps.org/pre/abstract/10.1103/PhysRevE.94.043103. Please refer to any applicable terms of use of the publisher. University of Bristol -Explore Bristol Research General rightsThis document is made available in accordance with publisher policies. Please cite only the published version using the reference above. Full terms of use are available: http://www.bristol.ac.uk/pure/about/ebr-terms PH… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
20
2

Year Published

2018
2018
2020
2020

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 10 publications
(25 citation statements)
references
References 21 publications
3
20
2
Order By: Relevance
“…However, the gap ratio of their set-up is smaller η = 0.8 and the Froude number is also higher F i = 0.5 than in the present experiment where F i = 0.2. Interestingly, Leclercq et al (2016) also report a high dominant azimuthal wavenumber m = 11 at instability onset when µ 0.5 for η = 0.9 and F i = 0.2.…”
Section: Experimental Observationsmentioning
confidence: 77%
See 4 more Smart Citations
“…However, the gap ratio of their set-up is smaller η = 0.8 and the Froude number is also higher F i = 0.5 than in the present experiment where F i = 0.2. Interestingly, Leclercq et al (2016) also report a high dominant azimuthal wavenumber m = 11 at instability onset when µ 0.5 for η = 0.9 and F i = 0.2.…”
Section: Experimental Observationsmentioning
confidence: 77%
“…Recently, Leclercq et al (2016) and Park et al (2017) have investigated the centrifugally unstable regime µ < η 2 by means of linear stability analyses. They both have shown that the strato-rotational instability continues to exist in this regime and is therefore in competition with the centrifugal instability.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations